Penerapan Perda Bernuansa Syariat Islam (Kajian tentang Penerapan Perda Bernuansa Syariat Islam di Bulukumba Sulawesi Selatan - Ashadi L Diab (Al-'Adl, 2009)
This research elaborates three points which are: what is the background of applying sharia Islam-bassed local regulation in Bulukumba? What are responses to applying it? And what are the effects for Muslims society and non-Muslims in Bulukumba? For achieving those purposes, this research uses a qualitative approach and data are analyzed through multistage and multilevel ways using purposive sampling. The ways for collecting data are documentation, observation, and in-depth interview. This research uses Arskal’s theory (level of operating sharia Islam).            The results of the research show that there are three background ideas for applying sharia Islam-based local regulation that is historical awareness, political factors and a social reality that neglect religious values.  After applying sharia Islam-based local regulation, the level of criminality decreased sharply. Based on my research, the applying sharia Islam-based local regulation just is able to practice in ordinary crime and never touch what called as the extraordinary crime of corruption. The district regulation also has had a bad effect on inter-religious relations